2018
DOI: 10.2147/opth.s183249
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent in refractive surgery: in-person vs telemedicine approach

Abstract: PurposeThe aim of this study was to compare the quality of consent process in refractive surgery between patients who had a preoperative consent discussion with the surgeon using a telemedicine approach and those who had a face-to-face discussion.MethodsPatients treated between January and December 2017 (8,184 laser vision correction [LVC] and 3,754 refractive lens exchange [RLE] patients) that attended day 1 and 1-month postoperative visit were retrospectively reviewed. Preoperative consent preparation includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This model has been used to evaluate physicians' acceptance of telemedicine technology (Hu, Chau, Sheng, & Tam, 1999), but no studies have used this model to evaluate teleconsent technologies. Studies previously evaluating patient's perceptions of telemedicine approach to consent versus paper-based consent reported that patients preferred the telemedicine approach (Schallhorn, Hannan, Teenan, Pelouskova, & Schallhorn, 2018). Several methods have been developed to investigate patient and provider perception of various consent forms (Chalil Madathil et al, 2013;Khasawneh, Rogers, Bertrand, Madathil, & Gramopadhye, 2019;Welch et al, 2016) that will be used to perform this study.…”
Section: Research Gapmentioning
confidence: 99%
“…This model has been used to evaluate physicians' acceptance of telemedicine technology (Hu, Chau, Sheng, & Tam, 1999), but no studies have used this model to evaluate teleconsent technologies. Studies previously evaluating patient's perceptions of telemedicine approach to consent versus paper-based consent reported that patients preferred the telemedicine approach (Schallhorn, Hannan, Teenan, Pelouskova, & Schallhorn, 2018). Several methods have been developed to investigate patient and provider perception of various consent forms (Chalil Madathil et al, 2013;Khasawneh, Rogers, Bertrand, Madathil, & Gramopadhye, 2019;Welch et al, 2016) that will be used to perform this study.…”
Section: Research Gapmentioning
confidence: 99%
“…Patients who want to take a more active role in decision-making about their treatment are increasingly using the internet to seek information about their disease [8]. Achieving the right information from reliable sources increases patient satisfaction and can improve treatment results [9][10][11]. However, in our assessment of the quality of information presented in YouTube videos on FECD, we found that these videos provided only moderate-quality information about the disease.…”
Section: Discussionmentioning
confidence: 88%
“…Promising results of patient satisfaction with remote consenting for elective refractive surgery have been shown. 18 In addition, our previous experience with femtosecond laser assisted in situ keratomileusis (FS-LASIK) on the day of the first screening visit has affirmed the results of this procedure. 19 However, scant data are available regarding the clinical outcomes of Trans-PRK surgery completed during the day of the first consultation appointment in compared with a following visit.…”
Section: Introductionmentioning
confidence: 88%